Actual Issues of Treaty Law in CIS Countries - ZOZULYAK, Olga I.; OLIINYK, Oksana S.; SISHCHUK, Liliana V.; SLIPENCHUK, Nataliia A.; PARUTA, Yuliia I. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).35, 2019)
The development of social relations requires changes in various spheres of human activity and, accordingly, in the relations between the state and society, between the state and the individual. In addition, one of the effective regulators of these relations is a treaty, which can be used in various spheres. To date, the science has not developed a unified view of the contract, and its issues are discussed by representatives of various scientific fields, with the contract being studied as a legal fact, agreement, legal relationship, document and in this regard is defined differently. Moreover, contractual relationship is in constant flux and suffer from changes caused by various factors of legal validity. Therefore, treaty law and the rules governing contractual obligations are given a great deal of attention during improving the process of reforming civil law and ensuring its further effective implementation in the CIS. Within the framework of the conducted research and comparative analysis of the legal bases and practice of application in the sphere of treaty law, the author has formulated grounded positions on the outlined and topical issues, which are as follows: (1) the peculiarities of the use of terminology in the context of the problem of interpretation of contract terms are revealed; (2) identified problems that arise during the termination of treaties in the CIS; (3) the influence of innovative technologies and globalization and the nature of contractual relations in the territory of the CIS countries are established; (4) approaches to ‘smart-contracts’ and a public contract are disclosed; (5) the discussion approaches to understanding the concept of ‘freedom of contract’ are analyzed; 6) a conditional list of the most pressing issues of contract law that arises in the CIS are formed.